Design and evaluation of cream-based formulations containing two organic materials for adsorbent, antimicrobial, antioxidant and anti-inflammatory properties (The East and Central African Journal of Pharmaceutical Sciences, 2026)
Activated charcoal and turmeric (Curcuma longa L.) powders, commonly used as medicines or spices, are considered valuable anti-aging agents. The aim of the study is to formulate activated charcoal and turmeric powders into Aqueous cream BP and assess for adsorbent, antioxidant, anti-microbial and anti-inflammatory properties. Activated charcoal and turmeric were characterized and twenty creams prepared with each powder alone and combined, were evaluated for organoleptic properties, viscosity, spreadability, antioxidant activity, stability and antimicrobial properties. Anti-inflammatory activity was evaluated using carrageenan-induced acute inflammatory model. Data was analyzed using ANOVA at α0.05. Creams containing 6%w/w activated charcoal and turmeric powders 3:1 gave comparable (p = 0.001) antioxidant and anti-inflammatory properties with the marketed sample and promising antimicrobial activities against Gram-positive and Gram-negative bacteria, and fungi. No change in stability occurred throughout the period of storage. Combination of turmeric and activated charcoal powders showed antioxidant, anti-microbial, anti-inflammatory, and adsorbent properties in cream formulations.
Keywords: Activated charcoal powder, Adsorbent, Anti-inflammatory property, Anti-microbial, Antioxidant, Aqueous cream BP, Turmeric powder